Identification of a new promoter for the response regulator rcsB expression in Salmonella enterica serovar Typhimurium - Pescaretti, María de Las Mercedes (2009)
The RcsCDB (Rcs) phosphorelay system regulates capsule synthesis,flagella production and other cellular activities in several enteric bacteria. This system consists of three proteins: the sensor RcsC, the cognate response regulator RcsB and the histidine-containing phosphotransfer protein RcsD (YojN), which is hypothesized to act as an intermediary in the phosphotransfer from RcsC to RcsB. The rcsC gene is convergently transcribed toward rcsB, which follows rcsD in what appears to be a two-gene operon. Here, it is reported that the overproduction of the rcsB gene represses rcsD transcription, but has a weak effect on its own expression. We demonstrated that the differential rcsD and rcsB expression is due to the activity of two promoters to transcribe the rcsB gene: (1) PrcsDB located upstream of rcsD and (2) PrcsB located within the rcsD coding region. In addition,here it was demonstrated that in Salmonella typhimurium, PrcsB is important to activate the rcsB expression during the stationary growth phase.